New Dynamics of Disability and Rehabilitation Interdisciplinary Perspectives - Harsløf, Ivan.; Poulsen, Ingrid; Larsen, Kristian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This collection provides a broad coverage of recent changes in medical and vocational rehabilitation in Northern Europe. It presents analyses that cut across health sciences, medical sociology, disability studies and comparative welfare state research. Through this interdisciplinary perspective, the book explores the changing roles of patients, caregivers, professionals and institutions, and the wider implications of these changes for social inequalities in health. What obstacles do different groups of patients encounter when negotiating the complex chains of medical and vocational services? Who decides regarding references to specialized treatments, and the provision of comprehensive and coordinated services, and different types of benefits and material support? What is the importance of the resources that patients and caregivers bring to bear in the rehabilitation process?
1. Introduction: New dynamics of Disability and Rehabilitation -- 2. Northern European Rehabilitation Services in the Context of Changing Healthcare, Welfare, and Labour Market Institutions: A Theoretical Framework -- 3. The Post-corporatist Rehabilitation System in Germany: High Potential, Critical Moments -- 4. From Quotas to Sanctions: The Political Economy of Rehabilitation in the UK -- 5. The Redesigning of Neurorehabilitation in Denmark and Norway -- 6. Rehabilitation as a Reformed Governance Technology: Freedom, Constraint, and Concealment -- 7. Return to Work After Severe Traumatic Brain Injury in Diverse Labour Market and Welfare State Contexts -- 8. Severe Brain Injury and Boundary Work -- 9. Conversion of Social Capital in the Rehabilitation Process of Adolescents Following an Acquired Brain Injury -- 10. Complex Problems in Need of Inter-organizational Coordination: The Importance of Connective and Collaborative Professionalism within an Organizational Field of Rehabilitation.-11. Transfer Practices during Acquired Brain Injury Rehabilitation: A Descent in the Medical Hierarchy -- 12. Rehabilitation as a Curricular Construction -- 13. Interdisciplinarity and Rehabilitation Research.
Keywords: Social medicine; Medical policy; Medical Sociology; Health, Medicine and Society; Health Policy